Tunable dual-wavelength filter and its group delay dispersion in domain-engineered lithium niobate - Guang-hao Shao; Jing Song; Ya-ping Ruan; Guo-xin Cui; Yan-qing Lu (AIP Advances, 2016)
A tunable dual-wavelength filter is experimentally demonstrated in domain-engineered lithium niobate. Application of an electric field on the y-surfaces of the sample results in the optical axes rotating clockwise and anticlockwise, which makes selective polarization rotation. The quasi phase-matching wavelengths could be adjusted through suitable domain design. A unique dual valley spectrum is obtained in a periodically poled lithium niobate structure with a central defect if the sample is placed between two parallel polarizers. The expected bandwidth could be varied from ∼1 nm to ∼40 nm. Moreover, both the spectral response and group delay dispersion could be engineered.